Analyse comparative de la politique fiscale des prix de transfert au Maroc par rapport aux principes de l'OCDE - CHAIHAB Saida; ABKAR Youssra (African Scientific Journal, 2024)
Abstract: The growth of multinational groups is a direct result of the internationalization of economies, this global trend has incentivized companies to seek opportunities and expand their operations beyond the confines of their home countries. As businesses become more globally interconnected, the need for comprehensive and strategic tax policies becomes evident. Among these, the transfer pricing tax policy plays a pivotal role. It is specifically formulated to deter corporations from engaging in the practice of artificially shifting profits from one subsidiary to another, a practice often attempted with the aim of minimizing the corporation's total tax liability across various countries. By ensuring that transactions between subsidiaries are conducted at arm's length – that is, in a manner consistent with transactions between unrelated parties – this policy aims to uphold the integrity of tax systems and prevent tax evasion, thereby promoting a more equitable distribution of tax obligations among multinational entities. This article conducts a detailed comparative analysis of the Moroccan transfer pricing tax policy against the principles established by the Organization for Economic Co-operation and Development (OECD). It also explores the evolution of Moroccan legislation and the proposed reforms in transfer pricing tax policy. The text addresses the traditional and transactional methods used to evaluate the commercial and financial relationships between associated enterprises. The article also highlights the challenges and limitations of advance pricing agreements in transfer pricing, offering a critical perspective on the efforts to align Moroccan regulation with OECD guidelines. The analysis showed that the Moroccan framework on transfer pricing diverges from the OECD's recommendations, notably due to a lack of precise guidelines and the absence of rules for specific cases. However, this Moroccan policy demonstrates partial alignment with the OECD guidelines, particularly through the adoption of the arm's length principle and the possibility of advance agreements. Keywords: International taxation, Fiscal policy, Multinationals, OECD, TP (Transfer Pricing), Arm's length principle, Morocco. Résumé : La croissance des groupes multinationaux est directement liée à l'internationalisation des économies. Cette tendance mondiale a encouragé les entreprises à rechercher des opportunités et à étendre leurs opérations au-delà des limites de leurs pays d'origine. Avec l'interconnexion croissante des entreprises à l'échelle mondiale, le besoin de politiques fiscales complètes et stratégiques devient manifeste. Parmi celles-ci, la politique fiscale en matière de prix de transfert occupe un rôle central. Elle est spécifiquement conçue pour dissuader les entreprises de se livrer à la pratique consistant à transférer artificiellement des bénéfices d'une filiale à une autre, dans le but de minimiser la responsabilité fiscale totale de l'entreprise à travers différents pays. En garantissant que les transactions entre filiales soient conduites à longueur de bras – c'est-à-dire, de manière conforme aux transactions entre parties non liées –, cette politique vise à préserver l'intégrité des systèmes fiscaux et à prévenir l'évasion fiscale, favorisant ainsi une répartition plus équitable des obligations fiscales parmi les entités multinationales. Cet article réalise une analyse comparative détaillée de la politique fiscale marocaine en matière de prix de transfert par rapport aux principes établis par l'Organisation de Coopération et de Développement Économiques (OCDE). Il explore également l'évolution de la législation marocaine et les réformes proposées concernant la politique des prix de transfert. Le texte aborde les méthodes traditionnelles et transactionnelles utilisées pour évaluer les relations commerciales et financières entre entreprises associées. En conclusion, l'article souligne les défis et limitations des accords préalables sur les prix de transfert, offrant une perspective critique sur les efforts déployés pour harmoniser la réglementation marocaine avec les directives de l'OCDE. Mots clés : Fiscalité internationale, Politique fiscale, Multinationales, OCDE, APP, Principe de pleine concurrence, Maroc.